Educação e destino das meninas desvalidas do Orphanato D. Ulrico: no cenário da cidade da Parahyba (1913-1929) - Nascimento, Roberta Maria Aguiar do (2015)
The main objective of this dissertation is to comprehend the D. Ulrico Orphanage as an educational institution that took responsibility over the education of unprivileged girls in the Parahyba city in the conjecture of speech to civilize, modernize and sanitize the city. The institution now presented will be visualized taking into consideration the society of Paraiba in the early XX century (in the historic period corresponding to the year between 1913 to 1929). For both shared ideals about unprivileged women and education. The Orphanage is understood as a socio-historical production of the Parahyba city in the studied period. For such understanding, a few authors were referenced, such as Dermeval Saviani (2007), Justino Magalhães (2004), Castanho (2007), Farias (1997) and Nascimento (2013). The educational institution executed a double movement in the preparation of the younglings, offering them content and ideologies with the intent of acceptation of the imposed law and discipline. Starting from the option to analyse the profile of the internees it was attempted to unravel the type of education that was defended for unprivileged young women in the early XX century in Parahyba do Norte. The realization of his study utilized the following sources: enrolment files of the internees from the years 1922 to 1929; the Record of the May the 23rd of 1922 General Assembly; Records of the Protector and Permanent Commissions; Statutes of Protector and Permanent Commissions from 1913; and exemplars of the A Imprensa newspaper from 1913 to 1928. The profile of woman advocated by the managers of the D. Ulrico Orphanage indicated that she was to be educated to care for the home, the children and the husband. It showed proximity to the ideals present in the society of that period. Such manner of comprehension about women, especially those of lower classes, became natural and turned into a culture that dictated the ways and manners of the young women who attended the institution conditioned by their social origins. Since very early, the internees were to have an education exclusively related to domestic duties. They did not need to develop habits and mores considered modern once their society roles did not require civilizing skills. What could be found, from the documents analysis, indicates that the internees had an education directed to house duties. Moreover, upon leaving the institution they would go work on the houses of the Orphanage’s benefactor associates only in exchange for shelter and food. Therefor indicating a delineated fatality in the fate of these young unprivileged women.